Pemanfaatan Penginderaan Jauh (PJ) dan Sistem Informasi Geografis (SIG) Untuk Menentukan Tingkat Bahaya Erosi (TBE) DAS Bodri - YUDHATAMA S, Adhika ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Remote sensing use in the process of tapping the various characteristics of the field of information and some of the other variables, namely land use and slope. Information field characteristics are qualitatively interpreted from ALOS AVNIR - 2 imagery has advantages over the spectral aspects are pretty good. Geographic Information Systems play a role in the processing of the data that has been generated from remote sensing information and other secondary data. Universal Soil Loss Equation ( USLE ) is used to predict watershed erosion Bodri. Necessary parameters are erosivity, erodibility, slope length and slope, vegetation cover index and the index of conservation. By using USLE all these parameters in overlay so get annual erosion rate value. Calculation results of erosion potential Bodri watershed there are three levels , namely very light , light and medium. Very light around 0,000952-14.82 tonnes / ha / year , lighter around 15.20-58.12 tons / ha / year and were about 62.61-107.99 tonnes / ha / year .